Anthropology of Los Angeles : place and agency in an urban setting - Banh, Jenny (Lexington Books, 2017)
"The Anthropology of Los Angeles : Place and Agency in an Urban Setting questions the production and representations of both the real and imagined L.A. by documenting hidden histories that portray a collision of race, class, gender, identity, food, and space"--Provided by publisher